1990
DOI: 10.1084/jem.172.6.1877
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive expression of pore-forming protein in peripheral blood gamma/delta T cells: implication for their cytotoxic role in vivo.

Abstract: SummaryThe cytotoxic activity and pore-forming protein (PFP) expression of human peripheral blood (PB) y/S T cells were examined. Fresh y/S T cells isolated from PB lymphocytes by fluorescenceactivated cell sorting exhibited a substantial natural killer-like cytotoxic activity against K562 target cells and had a high cytotoxic potential triggered by anti-CD3 monoclonal antibody (mAb) against P815 target cells bearing FcyR. Immunocytochemical staining with an anti-PFP mAb revealed that virtually all PB y/S T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
45
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 16 publications
0
45
0
Order By: Relevance
“…In this study, we first investigated PFP + cells and their phenotypes in circulating PBL by double staining, using both a rat anti-PFP monoclonal antibody which cross-reacts to human PFP (Nakata et al, 1990) (Rabinowich et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we first investigated PFP + cells and their phenotypes in circulating PBL by double staining, using both a rat anti-PFP monoclonal antibody which cross-reacts to human PFP (Nakata et al, 1990) (Rabinowich et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Expressed by natural killer (NK) cells, ␥␦ ϩ T cells, CD8 ϩ cytotoxic T lymphocytes (CTLs), and some other T-cell subsets (9)(10)(11), pfp is essential for delivery of proapoptotic granzymes, which initiate the destruction of virus-infected or transformed cells (12)(13)(14). We have previously demonstrated that approximately half of a cohort of aging pfp-deficient mice developed spontaneous mature B-cell lymphomas between 300 and 750 days from birth (15)(16)(17).…”
mentioning
confidence: 99%
“…Pore-forming proteins are constitutively expressed by peripheral blood cdT cells, 34 suggesting that these proteins play a vital role in cdT-cell cytotoxicity. Moreover, Vc9d2T lymphocytes were reported to kill microorganisms residing in intracellular compartments in a perforin and granzyme-dependant manner.…”
Section: Discussionmentioning
confidence: 99%